2001
DOI: 10.1007/s11661-001-0167-x
|View full text |Cite
|
Sign up to set email alerts
|

New discoveries in deformed metals

Abstract: Microstructural analysis by advanced and automated methods has allowed deformation microstructures to be quantified in terms of common structural parameters. This quantification has shown for a variety of materials and processing conditions that the microstructural evolution follows a universal pattern of grain subdivision from the macroscale to the nanometer scale. This microstructural evolution has been described empirically and in theoretical models based on general principles for the formation of dislocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
205
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(217 citation statements)
references
References 93 publications
9
205
1
2
Order By: Relevance
“…(1). The dislocation density (ρLAB) can be estimated based on the misorientation angle (θ): ρLAB =1.5θSv/b, assuming that the boundaries are mixed boundaries [1]. The contribution from HABs (Eb) can be the product of surface area per unit volume (Sv=1/DT+π/(2DL)) [10] and the boundary energy per unit area (γ) [13]:…”
Section: Structural Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…(1). The dislocation density (ρLAB) can be estimated based on the misorientation angle (θ): ρLAB =1.5θSv/b, assuming that the boundaries are mixed boundaries [1]. The contribution from HABs (Eb) can be the product of surface area per unit volume (Sv=1/DT+π/(2DL)) [10] and the boundary energy per unit area (γ) [13]:…”
Section: Structural Heterogeneitymentioning
confidence: 99%
“…Plastic deformation of metals is intrinsically heterogeneous, and different grains or different parts of one grain are usually subjected to different deformations and in turn distinct microstructures and textures are formed [1,2]. As is the main theme of this symposium, structural heterogeneity is of greatly scientific and technological importance in terms of the structural adjustment for property optimization in particular for nanometals with high strength but low ductility and low thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The recrystallized-equiaxial grains at ARB 0c are elongated along RD by roll bonding at each ARB process, and grain thickness is continuously reduced with increasing n. At the same time, the fraction of HAGBs seems to increase after ARB 8c. size evolution of ARB processed 2N-Al 21) , which is known as grain subdivision during SPD processes 22) . Figure 5 (a)-(h) show the {111} PFs constructed from EBSD data of ARB 0c -ARB 15c, and, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Deformation-induced microstructures have been extensively investigated in deformed metals and alloys, and many microstructural features have been reported to be common to both cold and hot deformation, e.g., cell blocks, cells, dense dislocation walls, and subgrains [23]. It is also found that, during cold deformation, a microband structure starts to appear when the strain reaches a certain value [24][25][26][27].…”
Section: Microstructure Formed Around Pin Toolmentioning
confidence: 99%